Faktor- Faktor Yang Mempengaruhi Consumer Buying Behavior Terhadap Penjualan Properti di Kota Batam - Hasan, Golan (Journal of Accounting and Management Innovation, 2017)
This research aims on analyzing components effecting customer buying behavior which is measured by brand image, advertisement, service quality, and price on customer buying behavior.Â  The research object is population of Batam city. Using probability sampling method, samples that meet the requirements are 300 respondence. The data are then analyzed using Statistical Package for Social Sciences (SPSS). The result indicates that advertisement have no significance effect on customer buying behavior. While brand image, service quality, and price have significance effect on customer buying behavior. Keywords: Brand Image, Advertisement, Service Quality, Price, Customer Buying Behavior